Content analysis of the Woman's Home Journal's portrayal of the modern home (1935-1939, 1946-1948) - Nocon, Nica Noelle L.
Limited information on the historical development of interior spaces in the Philippines has made magazines a valuable resource for gaining insights. An example is the Woman’s Home Journal, one of the earliest women’s magazines in the Philippines, which provides a glimpse into the concept of a modern home interior during the early twentieth century through its Household Hints (later Household Notes) column. This qualitative content analysis identified the recommendations for modernizing home interiors in the Household Hints/Notes column, and analyzed the key aspects and elements that have been highlighted in the column as well as the portrayal of the modern home interior space. The Woman’s Home Journal, released monthly in the years 1935-1939 and 1946-1948 is the primary source of data for this study. Through purposive sampling, only accessible magazine issues were selected for the study. Data was analyzed using thematic analysis, which is in line with qualitative content analysis. Findings show that the recommendations to modernize the home can be grouped into four broad themes, each with respective sub-themes: 1) efficiency (multifunctionality, maximization of space, spatial quality, and optimal flow); 2) regulated access (privacy and openness); 3) practicality (affordability, workability, and resourcefulness); and 4) visual harmony (balance, pattern/print, ambiance, and color). The aspects and elements of the home interiors that were highlighted in the themes are furnishings, furniture, layout and zoning, and materials. Lastly, the magazine, through its Household Hints/Notes column, portrays the modern home interior as an efficient space with regulated access to some private areas, practical and affordable, and with visual elements that harmonize well.